Subjective time under altered states of consciousness in ayahuasca users in shamanistic rituals involving music - Campagnoli, A.P.S. (Braz J Med Biol Res, 2020)
Ayahuasca is described as a hallucinogenic substance whose property is to alter the subjective experience of time and impair the perception of the passage of time during stimuli of more than two to three seconds. The dose-dependent effects of two concentrations of ayahuasca in the ritualistic context were investigated employing temporal reproduction tasks in participants experienced in shamanistic ayahuasca rituals. The study was conducted on nine healthy volunteers who ingested two doses of ayahuasca at two times during a ritual session. The doses of each session, consumed in amounts ranging from 20 to 60 mL, were either of low concentration or of experimental ayahuasca according to a double-blind procedure. Participants performed the task of immediately listening and reproducing, with a laptop, 20-s musical stimuli during the session. The results showed that significant temporal distortion was triggered by the musical stimulus presented without the ingestion of ayahuasca, with means of 16.33 to 16.52 s. There were minor temporal distortions after ingestion of ayahuasca: a mean of 17.91 s for control ayahuasca and of 18.38 s for experimental ayahuasca. These results with less temporal distortion among participants with ayahuasca intake disagree with other studies of hallucinogens involving temporal reproduction.